Penerapan Media Matching Puzzle untuk Meningkatkan Keaktifan dan Pemahaman Siswa Kelas VII MTs Mambaul Ulum - Muhammad Mufti Eka Prasetyo; Chaeril Anam; Dzarratun Khairunnisa; Anggi Wijayanto; Abdul Wahab (Kampus Akademik Publiser, 2026)
This study aims to address the problems that occur in Grade VII students of MTs Mambaul Ulum. The approach used is Classroom Action Research (CAR), a study consisting of repeated stages. This study was designed to provide solutions to the problems that occur, by selecting learning media that can help solve problems in the classroom in the form of Matching Puzzle Media based on the material Regarding Parts of a Book. Before using Matching Puzzle Media, this study found data in the form of an average percentage of student activity of 36% and student understanding of 37%. After carrying out class actions, Matching Puzzle Media can increase the value of activity by 26% and student understanding by 14% in Cycle I. When continued in the next Cycle, this media increased the value of activity by 19% and understanding by 30%.